Peran Financial Technology Dalam Meningkatkan Literasi Keuangan Pada Generasi Z - Wulan Ariani Damayanti; Risa Ratna Gumilang (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Technological progress is a new driver of economic growth, if it is related to the financial sector, financial technology has been able to become a new instrument with the hope of increasing financial growth. This research aims to determine the role of financial technology in increasing financial literacy in generation Z . This research uses a qualitative descriptive research method, research that includes an arrangement of interpretative techniques with understanding, not the frequency, of phenomena that often or rarely occur naturally in the social world. The research results show that all respondents know the term financial technology (fintech) and the fintech applications commonly used by generation z are Gopay, OVO, Shopee Pay, Dana. Regarding financial literacy, respondents are in the less literate category, only having limited knowledge about financial institutions, financial products and services. Special education is needed so that literacy regarding fintech and financial literacy continues to increase.